The influence of electronic word of mouth on Instagram users: An emphasis on consumer socialization framework - Narges Delafrooz; Yalda Rahmati; Mehrzad Abdi (Cogent Business & Management, 2019)
The present study aimed at exploring the extent to which users model their behavior-as well as their brand attitudes, their perception of relationship quality, their use of Instagram, and the number of brands they follow-on other users. This distinction can help marketers and social media experts discover the most likely perspectives of brand management. The statistical population was composed of the users of the Instagram social network, out of which 384 individuals were sampled by convenience non-probable technique. The hypotheses were tested by the logistic regression analysis. The results show that peer communications, brand attitude, brand relationship quality, and Instagram usage influence the manifestation of eWOM in the Instagram social network. The paper is concluded with some recommendations to marketers in the context of the Instagram social network.
Keywords: 650; consumer socialization; electronic word of mouth; brand; Instagram; social network; logistic regression analysis